The Efficacy and Safety of Cytarabine on Newly Diagnosed Primary Central Nervous System Lymphoma: A Systematic Review and Meta-Analysis - Zheng, Xiaohong; Yang, Shoubo; Chen, Feng; Wu, Si; Li, Wenbin (Frontiers in Oncology, 2020)
Background: The role of cytarabine on newly diagnosed primary central nervous system lymphoma (PCNSL) remains controversial. The present study mainly aimed to assess the efficacy and safety of cytarabine in the treatment of PCNSL. Methods: We systematically searched PubMed, Embase and the Cochrane library for randomized controlled trials comparing treatment of PCNSL patients with or without cytarabine. A meta-analysis was conducted to compare the odds ratios (ORs) with corresponding 95% confidence intervals (95% CI) for complete remission (CR) rate, overall response rate (ORR) and grade 3–4 toxic effects, hazard ratios (HRs) with 95% CIs for progression-free survival (PFS) and overall survival (OS) using Stata 12.0. Results: In total, three randomized clinical trials were analyzed in this study. The result of our statistical analysis demonstrated that the application of cytarabine was closely correlated with a higher CR (OR: 2.27, 95% CI: 1.29-3.99,P < 0.01) and ORR (OR: 2.11, 95% CI: 1.14-3.93, P = 0.02). No significant difference was found in OS (HR: 0.75, 95% CI: 0.50-1.13, P = 0.17), but PFS had been improved (HR: 0.66, 95% CI: 0.45-0.97, P = 0.04) when cytarabine was added to the treatment regimen. The grade 3-4 side effects rate of the cytarabine group was higher (overall OR: 2.95, 95% CI: 1.37-6.34, P < 0.01) than the cytarabine-free group. Conclusions: This meta-analysis verifies that adding cytarabine to the therapeutic regimen is helpful for newly diagnosed PCNSL patients in terms of CR, ORR and PFS. Moreover, it should be noted that the grade 3-4 toxic effects, especially hematological toxicity is higher in cytarabine group than cytarabine-free group. The results indicate that cytarabine plays an important role in the treatment of PCNSL.